UiTM Pro-Chancellor's visits - Wee, Roselind (Corporate Communications & International Relations, 2015)
On 26th August, 2014, the Pro-Chancellor of Universiti Teknologi MARA (UiTM). Tan Sri Datuk Seri Panglima Dr. Abdul Rahman Arshad accompanied by the Rector of UiTM Sarawak, Professor Dato Dr. Jamil Haji Hamali and the Deputy Vice Chancellor Academic Affairs and Research of UCSI, Professor Dr. Teoh Kok Soo paid a courtesy call to the Head of State, His Excellency, Tun Pehin Sri Haji Abdul Taib Mahmud. On the next day, a courtesy call was made to the Chief Minister of Sarawak, Yang Amat Berhormat Datuk Patinggi Tan Sri (Dr) Haji Adenan bin Haji Satem.